PENGARUH ARTIFICIAL INTELLIGENCE TERHADAP CUSTOMER EXPERIENCE (Survey pada Pengguna Aplikasi Spotify di Jatinangor) - Jumanul Qalby Khutami; Nadira Adinda Putri Asmara; Lina Auliana; Sam'un Jaja Raharja; Marsha Aulia Hakim (Universitas Diponegoro, 2024)
The business trend in Indonesia is toward developing artificial intelligence (AI), driven by technological advancements and customer demand for a more efficient experience. The entertainment industry, including music streaming, is experiencing rapid growth. Spotify, a leader in music streaming, uses AI to provide personalized recommendations to users. Despite this, some users report issues such as billing and app navigation. This study focuses on the influence of AI on user experience in the context of Spotify. This study uses a descriptive verification method to examine the effect of artificial intelligence (AI) on customer experience in using the Spotify application in Jatinangor, Indonesia. The sample of this study was 100 samples in the Jatinangor area. Through data collection using a structured questionnaire, data analysis was conducted with SPSS 27.0, using a simple linear regression test after validity and reliability were tested. Classical assumption tests such as normality, linearity, and heteroscedasticity were performed before regression analysis. Using statistical analysis on a sample of 100 Spotify users in Jatinangor, it was concluded that artificial intelligence (AI) significantly influences the customer experience. Results show rejection of the null hypothesis, validating that AI significantly impacts user experience in the context of Spotify.Keywords: Artificial Intelligence; Customer Experience; Entertainment.Tren bisnis di Indonesia mengarah pada pengembangan kecerdasan buatan (AI), didorong oleh kemajuan teknologi dan permintaan pelanggan akan pengalaman yang lebih efisien. Industri hiburan, termasuk streaming musik, mengalami pertumbuhan pesat. Spotify, sebagai pemimpin dalam streaming musik, menggunakan AI untuk memberikan rekomendasi personal kepada pengguna. Meskipun demikian, beberapa pengguna melaporkan masalah seperti penagihan dan navigasi aplikasi. Penelitian ini berfokus pada pengaruh AI terhadap pengalaman pengguna dalam konteks Spotify. Penelitian ini menggunakan metode deskriptif verifikatif untuk mengkaji pengaruh kecerdasan buatan (AI) terhadap pengalaman pelanggan dalam penggunaan aplikasi Spotify di Jatinangor, Indonesia. Penelitian ini mengumpulkan 100 sampel di daerah Jatinangor. Analisis data dilakukan dengan menggunakan SPSS 27.0 setelah data dikumpulkan melalui kuesioner terstruktur. Pengujian dilakukan menggunakan uji regresi linier sederhana. Dengan menggunakan analisis statistik pada sampel 100 pengguna Spotify di Jatinangor, disimpulkan bahwa kecerdasan buatan (AI) memiliki pengaruh yang signifikan terhadap pengalaman pelanggan (customer experience). Hasil menunjukkan penolakan terhadap hipotesis nol, memvalidasi bahwa AI berdampak secara signifikan terhadap pengalaman pengguna dalam konteks aplikasi Spotify. Kata Kunci: Kecerdasan Buatan; Pengalaman Pelanggan; Hiburan.